Historical epistemology: origin and present state - Sayganova, Veronika S. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
Discusses the origins and current trends in the development of historical epistemology as a promising direction in the theory of knowledge. The problem field of historical epistemology is revealed. The main issues of historical epistemology are the study of the concepts of the theory of knowledge in historical development; the history of the development of objects of scientific knowledge; social, practical, methodological and technological conditions of cognition in historical and cultural dynamics. The conclusion is made that historical epistemology is an interdisciplinary theoretical direction of philosophical thought. This direction allows us to comprehensively study the interaction of sociocultural factors in the development of science, its methods, objects, theories, considering science as a cultural and social value.